Application of minimum phase wavelet for generation of synthetic seismic signals - Surekha, Yandamuri; Sai Prathyusha, Akety; S Ramesh, K; Koteswara Rao, S (International Journal of Engineering and Technology, 2018)
Seismic signals are analyzed by using different wavelet transforms to evaluate the magnitude of the signal. Through experimentation, it is reported that surface wave magnitude is greater than equals to three, it would affect the environment. In this paper, an attempt is made to apply minimum phase wavelet technique to analyze the seismic signals through minimum phase wavelets using CREWES data.